Effect of back-diffusion on the performance of an electrochemical hydrogen compressor. (3rd April 2020) - Chouhan, Ashish; Bahar, Bamdad; Prasad, Ajay K.
Abstract: Hydrogen offers the potential to decarbonize the automotive and stationary power sectors and is therefore expected to play an increasingly significant role in meeting global energy demand. However, due to its low volumetric and gravimetric energy densities, it is important to find methods to efficiently store hydrogen in order to grow the hydrogen economy. Storing hydrogen as a compressed gas could be achieved by electrochemical compression (ECC), which is a membrane-based alternative to conventional mechanical compressors. ECC can be superior to mechanical compressors because of its higher efficiency, lack of moving parts and noiseless operation. Here, we report on the ECC of hydrogen using a Nafion 115 membrane at room temperature. Pressure vs. time curves have been collected at various operating voltages, and a compression ratio of 150 has been achieved with a single cell at an operating voltage of 0.1 V. This work focuses on the loss in electrochemical compression efficiency due to back-diffusion. A theoretical formulation for the ECC process incorporating back-diffusion is proposed and validated by experiments. A robust definition for ECC efficiency that properly accounts for back diffusion is also proposed. Highlights: Electrochemical hydrogen compressor based on Nafion membrane was tested. Back-diffusion strongly affects performance of electrochemical hydrogen compressor. Theoretical formulation of the electrochemical compression process was established. Theoretical formulation, including back diffusion, validated by experimental data. Robust definitions of ECC efficiencies based on work and power were formulated.